A pilot study on serum lactoferrin in patients with mild versus severe acne in correlation with disease duration - Manal A Sharara; Heba M Diab; Abd El Rahman M Reda (Wolters Kluwer Medknow Publications, 2019)
Background Acne vulgaris (AV) is a chronic inflammatory disease of the pilosebaceous units. Lactoferrin (LF) is an iron-binding glycoprotein, which is known to have a role in decreasing inflammation and microbial infection. A few studies have reported that many of the patients with acne had acceptable therapeutic response to LF supplementation. However, no studies have directly assessed serum LF level in patients with acne. Objective To evaluate serum LF level in patients with severe versus mild acne in comparison with healthy controls. Patients and methods Serum LF was assessed using enzyme-linked immunosorbent assay in 40 AV patients comprising two subgroups; 20 mild and 20 severe cases, versus 20 healthy controls. Levels were correlated with disease duration. Results Mean serum LF levels were significantly higher in patients with AV than in healthy controls (P<0.001), and in patients with severe disease than with mild AV. Serum LF level was inversely correlated with disease duration. Conclusion Serum LF is directly related to acne severity, being elevated in severe rather than mild cases. Therefore, it could be of prognostic value. Serum LF level is higher in acute stages rather than chronic cases, denoting its possible role as a compensatory acute-phase reactant, to overcome the detrimental effects of acute inflammation.